Genipin-crosslinked fibrin seeded with oxidized alginate microbeads as a novel composite biomaterial strategy for intervertebral disc cell therapy. (August 2022) - Panebianco, Christopher J.; Rao, Sanjna; Hom, Warren W.; Meyers, James H.; Lim, Tiffany Y.; Laudier, Damien M.; Hecht, Andrew C.; Weir, Michael D.; Weiser, Jennifer R.; Iatridis, James C.
Abstract: Discectomy procedures alleviate disability caused by intervertebral disc (IVD) herniation, but do not repair herniation-induced annulus fibrosus (AF) defects. Cell therapy shows promise for IVD repair, yet cell delivery biomaterials capable of sealing AF defects and restoring biomechanical function have poor biological performance. To balance the biomechanical and biological demands of IVD cell delivery biomaterials, we engineered an injectable composite biomaterial using cell-laden, degradable oxidized alginate (OxAlg) microbeads (MBs) to deliver AF cells within high-modulus genipin-crosslinked fibrin (FibGen) hydrogels (FibGen + MB composites). Conceptually, the high-modulus FibGen would immediately stabilize injured IVDs, while OxAlg MBs would protect and release cells required for long-term healing. We first showed that AF cells microencapsulated in OxAlg MBs maintained high viability and, upon release, displayed phenotypic AF cell morphology and gene expression. Next, we created cell-laden FibGen + MB composites and demonstrated that OxAlg MBs functionalized with RGD peptides (MB-RGD) minimized AF cell apoptosis and retained phenotypic gene expression. Further, we showed that cell-laden FibGen + MB composites are biomechanically stable and promote extracellular matrix (ECM) synthesis in long-term in vitro culture. Lastly, we evaluated cell-laden FibGen + MB-RGD composites in a long-term bovine caudal IVD organ culture bioreactor and found that composites had low herniation risk, provided superior biomechanical and biological repair to discectomy controls, and retained anabolic cells within the IVD injury space. This novel injectable composite hydrogel strategy shows promise as an IVD cell delivery sealant with potentially broad applications for its capacity to balance biomechanical and biological performance.